Aspek Perkembangan Manajemen Pembelajaran: Active Learning - M. Shohibul Aziz (Intizam, Jurnal Manajemen Pendidikan Islam, 2018)
The development of education in Indonesia is basically always interesting to observe and discuss. The concrete challenge lies in how to prepare human resources in this case teachers to manage learning. Because quality learning other than highly dependent on student motivation, also depends on the creativity of teachers.In its development, many models, strategies and learning techniques that can be selected as an alternative teacher to manage learning as well as develop creativity. One of the learning models is Active Learning or active learning.This active learning is based on the epistemology of constuctivism that emphasizes how one learns. How one develops his understanding and knowledge of the world around him by recognizing the objects around him that are reflected through his experience. When discovering something new, it is hoped that someone can reconstruct it with initial ideas and previous experiences.In line with the above basic concept, in Government Regulation no. 19 on National Education Standards, article 19, paragraph (1) states that "The learning process in educational units is organized interactively, inspiration, fun, challenging, motivating students to participate actively, providing sufficient space for initiative, creativity and independence according to talent, interest and physical and psychological development of learners. "Therefore, active learning models and overall strategies and techniques need to be applied and developed by teachers to manage learning for better and better quality.